Camalexin Quantification in Arabidopsis thaliana Leaves Infected with Botrytis cinerea - Daniel Savatin; Nora Bisceglia; Matteo Gravino; Claudia Fabbri; Daniela Pontiggia; Benedetta Mattei (Bio-Protocol, 2015)
Phytoalexins are heterogeneous low molecular mass secondary metabolites with antimicrobial activity produced at the infection site in response to pathogen invasion and represent an important part of the plant defense repertoire. Camalexin (3-Thiazol-2′-yl-indole) is a known phytoalexin first detected and isolated in Camelina sativa, from which it takes its name, infected with Alternaria brassicae (Browne et al., 1991). Production of camalexin is also induced in Arabidopsis thaliana leaves by a range of biotrophic and necrotrophic plant pathogens (bacteria, oomycetes, fungi and viruses) (Ahuja et al., 2012) as well as by abiotic stresses, such as UV and chemicals (e.g. acifluorfen, paraquat, chlorsulfuron and α-amino butyric acid) (Zhao et al., 1998; Tierens et al., 2002). Camalexin originates from tryptophan and CYP79B2 and CYP71B15 (PAD3) are P450 enzymes that catalyze important steps in its biosynthetic pathway (Glawischnig, 2007). The detection and quantification of camalexin content is required to understand how it is produced upon various stress conditions. Here we describe an easy method for camalexin extraction from Arabidopsis leaves infected with the necrotrophic fungus Botrytis cinerea, and further determination of camalexin levels by liquid chromatography–mass spectrometry (LC-MS). The method is sensitive enough to trace amount of camalexin down to the low pico-gram (10 pg/mg FW) range.